UJI pH DAN ORGANOLEPTIK SUSU SAPI PASTEURISASI DENGAN PENAMBAHAN BIJI CHIA - Mamluatunnajah, Ngafifah; Nunur Nuraeni (Nusantara Hasana Journal, 2025)
This study aimed to determine the effect of adding chia seeds (Salvia hispanica L.) on the organoleptic quality and pH of pasteurized cow's milk, and to determine the optimal concentration acceptable to consumers. The study was conducted in Sumberadi Village, Kebumen District, Kebumen Regency, from May to June 2025 using a Completely Randomized Design (CRD) with four treatments (0%, 1%, 2%, and 3% chia seeds) and four replications. Parameters tested included color, aroma, taste, texture, preference, and pH. Organoleptic testing was conducted by 20 semi-trained panelists using a four-level hedonic scale. The results indicated descriptive changes in sensory characteristics and pH due to the addition of chia seeds, particularly in color, taste, and texture. However, statistical analysis (ANOVA) showed no significant effect (p > 0.05) on any of the tested parameters. The pH tended to decrease with increasing chia seed concentration, but remained within safe limits. Treatment P0 achieved the highest score, while P1 demonstrated the best texture results, still acceptable to panelists. In conclusion, chia seeds can be added to pasteurized cow's milk at a maximum concentration of 1% to produce a product that maintains functional value without compromising the milk's sensory quality and pH.